Toward Zero Emission Maritime Transport: A Systematic Review of Decarbonization and Pollution Prevention in WIG Craft by Design - Arif Priadi, Antoni; Cahyadi, Tri; Winarno; Hadi, Miftahul; Sambega Bintang, Ananta; Dwikora Simanjuntak, Pargaulan; Barasa, Larsen; Suranta, Natanael; Rinaldi, Aditya (LPPM AKMI SUAKA BAHARI CIREBON, 2026)
The modern transportation sector must consider its environmental impact particularly air pollution in addition to improving efficiency and speed. One of the main factors contributing to air pollution and global warming is the exhaust emissions produced by fossil fuel-based modes of transportation. Wing in Ground (WIG) craft are vehicles that use ground effect to fly low over water or land with lower energy consumption than conventional aircraft. This is one alternative mode of transportation that is beginning to attract attention. The literature explicitly addressing the relationship between WIG Craft design and air pollution impacts remains relatively limited; therefore, studies need to be developed that explore preventive measures to minimize air and noise pollution from this technology. Research focusing on the potential pollution and environmental impacts generated by WIG Craft is still very limited; this is because WIG Craft is a technology not yet produced for public transportation, and another factor is that research focus remains on design, stability, and control. Given these conditions, this study is important for identifying and formulating preventive strategies to reduce air and noise pollution from the use of WIG Craft. Purpose – This systematic literature review aims to comprehensively synthesize the current evidence on pollution prevention strategies in WIG craft design. Methodology – The initial phase of the study involved a systematic literature review. This Systematic Literature Review investigation was guided by the PRISMA analysis. Because of its substantial data collecting and comparatively strict and precise process. Findings – The potential emissions from WIG craft can be reduced through the design of green propulsion systems using electric power and low-carbon fuels. To mitigate the environmental footprint of Wing-in-Ground craft, researchers have proposed a combination of advanced aerodynamic design, noise suppression technologies, and optimized operational strategies.